Experimental study and modeling of three grid-connected photovoltaic technologies of Meknes City - L. Bouhaki; R. Saadani; R. Agounoun; K. Sbai; M. Rahmoune (Institute of Advanced Engineering and Science, 2018)
Photovoltaic (PV) systems are the most promising renewable energy source in Morocco due to its abundant solar irradiation. The Moroccan government has launched various renewable energy programs to encourage the use of PV systems. In this work we present a comparative study in terms of energy produced and the efficiency of a grid connected photovoltaic (PV) system installed on the roof of the building occupied by the “Ecole Supérieure de Technologie de Meknes” (ESTM). The on-grid connected photovoltaic system has a total power of 5860 Watts (Wp). This system provides an average daily reduction of 30 kWh in the consumption of electrical energy at ESTM facilities; this will allow us to save fossil fuels and reduce emissions of greenhouse gas. The average annual production of electric power is estimated at 10.5 MWh, equivalent to burning 0.9 tons of oil, which will prevent the emission of about 2 tons / year of CO2 in the atmosphere. Three different commercial solar modules, manufactured with different materials and technologies in monocrystalline silicon, polycrystalline silicon and amorphous silicon were tested.